Engaging medical education scholars with a Twitter conference on professionalism and professional identity formation - DeWitt, Jessica M; Richards, Joslyn; Wald, Hedy S; Wyatt, TR; D'Eon, Marcel F (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Implication StatementThe Education Innovation Institute (EII) of Medical College of Georgia, Augusta University, hosted a conference on Twitter about Professional Identity Formation (PIF), #MCGConf2021PIF, on February 25, 2021. The conference featured five presentations by 15 authors from Canada and the U.S. A Twitter conference is a versatile, affordable, and accessible digital option for medical education groups interested in diversifying conference offerings and reaching a broader audience. It was low-cost, organized in six months, and garnered over 9,000 Twitter impressions. Small networks and interest groups can organize Twitter conferences for their constituencies and larger conference organizations can host online mini-conferences to supplement in-person events.